Hegemoni Wacana Kolonial dalam Cerpen “Mereka Bilang, Saya Monyet” karya Djenar Mahesa Ayu: Kajian Pascakolonial: Hegemony of Colonial Discourse in Short Story "Mereka Bilang, Saya Monyet" Written by Djenar Mahesa Ayu: Postcolonial Study - Iwan Saputra (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
Hegemony is the colonial’s effort done to legitimate its domination. By this hegemony, the colonizer is dominant to colonize. In this research, the writer attempts to elaborate about form and model of hegemony of colonial’s discourse in Djenar Mahesa Ayu’s short story “Mereka Bilang, Saya Monyet, by using postcolonial theory. To analyses this short story, the researcher would use the Homi K. Bhabha’s theory about postcolonial, that are stereotype, mimicry, and hybridity. The third concept is conducted to keep colonizer’s hegemony to colonized. The colonizer’s anxiety to colony encourages colonizer to do all effort to convince colonizer’s influence to colony. The colonizer attempts to do more ways by repetition of colonizer’s discourse. Based on the results of the analysis on their short story “Mereka Bilang, Saya Monyet”, the researcher found that the hegemony of colonial discourse was carried out by means of inculcating the identity of character “saya” who was considered a minority group. On the other hand, the mimicry made by character “saya” is an attempt to get recognition as a subject that has identity. The impersonation was a form of colonial discourse hegemony in character “saya” to make it look the same as “Kepala Anjing” representing the invaders. Repetition of the attitude shown by Kepala Anjing to character “saya” is a form of hegemony to convince.